BUDAYA ORGANISASI: SYSTEMATIC LITERATURE REVIEW DAN ANALISIS BIBLIOMETRIK - Kasfunnuri, M. Asren; Sopiah (Transpublika Publisher, 2022)
Organizational culture in Indonesia is still not considered as an important factor, in contrast to Japan and America which use organizational culture as a measure of company success. This study aims to determine the extent to which the influence of organizational culture on the organization. This research is a systematic literature review using the PRISMA and bibliometric methods. The findings show that organizational culture influences many organizational lines such as innovation, performance, strategy, etc. We suggest that companies take organizational culture as a consideration in making decisions.